1998
DOI: 10.1176/ajp.155.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Adult Psychiatric Status of Hyperactive Boys Grown Up

Abstract: The results of the present study are consistent with the authors' previously reported major findings. They strongly suggest that children with ADHD are at significantly higher risk for a specific negative course marked by antisocial and substance-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
396
2
21

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 657 publications
(458 citation statements)
references
References 30 publications
28
396
2
21
Order By: Relevance
“…International studies have shown that ADHD patients are at an increased risk for criminal activities [18]. However, these costs were expected to be low in the age group included in our study.…”
Section: Discussionmentioning
confidence: 89%
“…International studies have shown that ADHD patients are at an increased risk for criminal activities [18]. However, these costs were expected to be low in the age group included in our study.…”
Section: Discussionmentioning
confidence: 89%
“…1-6 For a significant proportion of children diagnosed with ADHD, their impairment will persist into adulthood. 7,8 Australian children are diagnosed with the disorder every day. For a significant number of these children, treatment with stimulant medication will ultimately be required.…”
Section: Introductionmentioning
confidence: 99%
“…By adulthood, 49-66% will have significant symptoms of the disorder or meet diagnostic criteria for it (Barkley et al, 2002;Mannuzza et al, 1993Mannuzza et al, ,1998Rasmussen & Gillberg, 2002;Weiss and Hechtman, 1993).…”
mentioning
confidence: 99%